A case report of synchronous bilateral tonsillar carcinoma associated with human papilloma virus - Shunji Tamagawa; Mehmet Gunduz; Keisuke Enomoto; Esra Gunduz; Kenji Warigaya; Muneki Hotomi (Journal of the Pakistan Medical Association, 2020)
The case of a 69-year-old man with bilateral synchronous tonsillar carcinoma is reported. The patient complained of nasal closure, strange voice, and discomfort in his pharynx when he was admitted to the Department of Otolaryngology Head and Neck Surgery at Wakayama Medical University, Wakayama, Japan, in March 2017. The palatine tonsils were enlarged and the surface was irregular. Left cervical lymphadenopathy was also evident. Histological examination from both tonsils was performed and bilateral tonsillar squamous cell carcinoma was diagnosed. PCR analysis showed the same HPV-DNA pattern from bilateral tonsils. Concurrent chemoradiotherapy was performed. Total 70 Gy of irradiation (2Gy/day×35 day) was applied to bilateral tonsillar tumours and upper neck. Follow up was conducted every three months and the patient was free of recurrence for three years. Patient’s informed consent was taken to publish the case report. Keywords: bilateral synchronous tonsillar carcinoma, HPV, tonsil Continuous...